Lactulose for the treatment of Chinese children with chronic constipation: A randomized controlled trial - Cao, Yuan; Liu, Shi-ming (Medicine (Baltimore), 2018)
This study aimed to investigate the efficacy and safety of lactulose for the treatment of Chinese children with chronic constipation. A total of 100 children with chronic constipation were included in this randomized controlled trial. They were equally and randomly allocated to a treatment group (n = 50) and a placebo group (n = 50). The participants in the treatment group received lactulose, while the subjects in the placebo group received placebo intervention. The children in both groups were treated for a total of 6 weeks. The primary outcome was daily stool frequency. The secondary outcomes consisted of stool consistency, measured by the Bristol Stool Form Scale, abdominal pain, flatulence, as well as the adverse events. All outcomes were measured at baseline and after 6-weeks treatment. After 6 weeks treatment, lactulose showed better outcomes in daily stool frequency (P < .01), and stool consistency (P < .01), except the abdominal pain (P = .24), and flatulence (P = .44), compared with the placebo. Additionally, no significant differences regarding all adverse events were detected between 2 groups. The results of this study found that lactulose is efficacious for Chinese children with chronic constipation after 6-weeks of treatment.